2021
DOI: 10.1021/acsami.1c08043
|View full text |Cite
|
Sign up to set email alerts
|

Specially Designed Polyaniline/Polypyrrole Ink for a Fully Printed Highly Sensitive pH Microsensor

Abstract: pH sensing for healthcare applications requires sensors with mechanically stable materials of high sensitivity and high reproducibility combined with low-cost fabrication technologies. This work proposes a fully printed pH sensor based on a specially formulated conducting polymer deposited on a microelectrode in a flexible substrate. A formulation, which combined polyaniline (PANI) and polypyrrole (PPy) with integrated polyelectrolyte poly(sodium 4-styrenesulfonate) (PSS), was specially prepared to be printed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
0
21
0
1
Order By: Relevance
“…Among the components of sweat pH sensors, the sensitivity and responsiveness of the flexible solid-contact ISEs fabricated through screen printing, spray-coating, drop-casting, and magnetron sputtering deposition techniques determine the performance of the wearable devices for ion sensing. The critical issues are the potential stability, the hydrophobicity of the transducing layer material (interfacial aqueous layer effect), and the interfacial redox/double-layer capacitance between the transducer and the ion-selective membrane (ISM). , A series of solid-contact functional materials are used as ion-to-electron transducing layer materials including conductive polymers, carbon-based materials, metal nanomaterials, and semiconducting metal oxides . Polyaniline (PANI) is a common conductive polymer with low cytotoxicity and is extensively used as a pH-sensitive material for detecting hydronium ions (H 3 O + ) through surface deprotonation. Carbon-based materials such as graphene and carbon nanotubes have been widely applied to pH sensor applications due to their structural controllability, high sensitivity, biocompatibility, and electrical characteristics. Gan et al through electrochemical lattice H + intercalation obtained WO 3 -based pH sensors with tunable sensitivity and selectivity . However, the continuous development of the high specific surface area and high capacitance nanomaterials used as solid-contact layers for pH sensors is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the components of sweat pH sensors, the sensitivity and responsiveness of the flexible solid-contact ISEs fabricated through screen printing, spray-coating, drop-casting, and magnetron sputtering deposition techniques determine the performance of the wearable devices for ion sensing. The critical issues are the potential stability, the hydrophobicity of the transducing layer material (interfacial aqueous layer effect), and the interfacial redox/double-layer capacitance between the transducer and the ion-selective membrane (ISM). , A series of solid-contact functional materials are used as ion-to-electron transducing layer materials including conductive polymers, carbon-based materials, metal nanomaterials, and semiconducting metal oxides . Polyaniline (PANI) is a common conductive polymer with low cytotoxicity and is extensively used as a pH-sensitive material for detecting hydronium ions (H 3 O + ) through surface deprotonation. Carbon-based materials such as graphene and carbon nanotubes have been widely applied to pH sensor applications due to their structural controllability, high sensitivity, biocompatibility, and electrical characteristics. Gan et al through electrochemical lattice H + intercalation obtained WO 3 -based pH sensors with tunable sensitivity and selectivity . However, the continuous development of the high specific surface area and high capacitance nanomaterials used as solid-contact layers for pH sensors is essential.…”
Section: Introductionmentioning
confidence: 99%
“…16 Polyaniline (PANI) is a common conductive polymer with low cytotoxicity and is extensively used as a pH-sensitive material for detecting hydronium ions (H 3 O + ) through surface deprotonation. 17 materials such as graphene and carbon nanotubes have been widely applied to pH sensor applications due to their structural controllability, high sensitivity, biocompatibility, and electrical characteristics. 20−22 Gan et al through electrochemical lattice H + intercalation obtained WO 3 -based pH sensors with tunable sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Zea et al also fabricated a flexible pH microsensor based on a mixed conductive polymer of PANI and PPy using inkjet printing (IJP) technology. 89 In a wide pH range (pH 3–10), the fully printed pH electrode showed a high sensitivity (81.2 mV per pH) and excellent reproducibility. Hryniewicz et al reported an impedimetric immunosensor for SARS-CoV-2 nucleocapsid protein monoclonal antibody detection by PPy–AuNP modified electrodes.…”
Section: Materials Engineering For Enhancing the Sensing Efficiency O...mentioning
confidence: 91%
“…Electrical Properties: The electrical properties of the strain sensors were evaluated using the same set-up previously used in our work. [51,52] Briefly, strain sensors were connected to four-point probe station (Figures S2 and S3, Supporting Information) that was connected to a source meter Keithley 2600. The sourcemeter was also connected to a PC for the obtention of the real-time data.…”
Section: Methodsmentioning
confidence: 99%